Microcystis aeruginosa and M. wesenbergii Were the Primary Planktonic Microcystin Producers in Several Bulgarian Waterbodies (August 2019) - Maya Stoyneva-Gärtner; Katerina Stefanova; Jean-Pierre Descy; Blagoy Uzunov; Mariana Radkova; Vera Pavlova; Mariya Mitreva; Georg Gärtner (Applied Sciences, 2020)
The rising interest in harmful cyanoprokaryote blooms promotes an increase of phycological and ecological research on potentially toxic species and their hazardous substances. The present study aimed to identify the main microcystin (MC) producers and their contribution to the phytoplankton of shallow waterbodies in Bulgaria, applying different methods. The sampling was performed in August 2019 in nine lakes and reservoirs, two of which (reservoirs Kriva Reka and Izvornik 2) were studied for the first time. The high contribution of cyanoprokaryotes to the total species composition and phytoplankton abundance was proved by light microscopic (LM) observations and HPLC analysis of marker pigments. The LM identification of potential MC-producers was supported by PCR amplification of mcyE and mcyB genes. The MCs amounts, detected by HPLC-DAD, varied by sites with a range from undetectable concentrations to 0.46 µg L−1 with only one recorded variant, namely MC-LR. It was found only in the reservoirs Mandra and Durankulak, while toxigenic MC-strains were obtained by PCR from five more waterbodies. Both LM and PCR demonstrated that the MC-producers were Microcystis aeruginosa and M. wesenbergii, despite their occurrence in low amounts (<0.5–5% of the total biomass) when filamentous cyanoprokaryotes dominated.